Interactions and co-pollution effects of fluorinated liquid crystal monomer and microplastics on aquatic sediment microbiota - Rui Yang; Sanjeeb Mohapatra; Apple Pui-Yi Chui; Season Si Chen; Mui-Choo Jong (Environmental Chemistry and Ecotoxicology)
Fluorinated liquid crystal monomers (FLCMs) are emerging aquatic pollutants that co-occur with microplastics (MPs); however, their combined ecological impacts remain poorly understood. This study investigated the interactions between a representative FLCM, 4-Ethoxy-2,3-difluoro-4′-(trans-4-propylcyclohexyl) biphenyl (EDPB), and four major types of MPs: polyethylene (PE), polypropylene (PP), polystyrene (PS), and polyvinyl chloride (PVC). The results revealed plastic-type-dependent adsorption capacities (PE > PS > PP > PVC; 380–850 μg/g) through distinct mechanisms: hydrophobic interactions predominantly influenced PE and PP adsorption, while π-π coordination enhanced PS binding. Microcosm experiments demonstrated that MP-EDPB composites significantly altered sediment microbiomes, showing consistent declines in Proteobacteria abundance (27–29 % vs 36.8 % in controls), pathogen enrichment in marine sediments (Acinetobacter 1.2 → 3.5 %; Vibrio 0.8 → 2.1 %), and ecosystem-specific functional disruptions. Notably, marine systems exhibited greater biodiversity shifts, while freshwater environments showed stronger nitrogen cycle inhibition. These findings provide mechanistic insights into FLCM-MP co-pollution effects on aquatic ecosystems. Environmental implication: Liquid crystal monomers (LCMs) and microplastics (MPs) are emerging contaminants that increasingly co-occur in aquatic ecosystems, yet their interactions and co-exposure risks remain poorly understood. This study demonstrated that the adsorption of LCMs onto microplastics was significantly influenced by plastic type, with equilibrium capacities (Qmax) following the order: PE (849.5 ± 1.2 μg/g) > PS (825.3 ± 0.8 μg/g) > PP (629.1 ± 0.3 μg/g) > PVC (380.2 ± 0.2 μg/g). The MPs-LCMs composites affected microbial composition and functions in sediments across both freshwater and seawater environments. These findings provide a quantitative basis for assessing the environmental partitioning and potential ecological risks associated with MPs-LCMs composite pollutants.